(untitled) (Research, Society and Development, 2022)
This study aims to discuss the gamification process and its contributions to mathematics teaching. This is a bibliographical research with scientific productions published between the years 2015 to 2020, supporting the description and reflection of such studies. The results show that, in view of a young audience inserted in digital technologies, in which games represent one of the most preferred segments of this audience, there is a need for contributions of pedagogical practices in the teaching of mathematics through the gamification process, contemplating the experienced reality by these young people today. In this sense, gamification has shown itself to be increasingly effective and efficient in teaching and learning mathematics for these young people in the educational context. Therefore, it is highlighted how much gamification contributes significantly to the teaching of mathematics, but it presents some difficulties that still need to be faced by teachers when it is used in the classroom.